Structural and optical characterization of Sm-doped ZnO nanoparticles - Okur, H. E.; Bulut, N.; Ates, T.; Kaygili, O. (Indian Acad Sciences, 2019)
Micro-structural changes in zinc oxide (ZnO) nanoparticles induced by the substitution of Zn2+ in ZnO by a rare earth (RE) metal ion, Sm3+, are investigated. Both pristine and Sm-doped ZnO with a nominal doping concentration of 1, 2 and 4% of Sm using a simple wet-chemical synthetic route followed by calcination at a high temperature of 900 degrees C, are synthesized. Structural investigations are primarily conducted using X-ray powder diffraction (XRPD) and scanning electron microscopy techniques. Evolution of structural parameters (unit cell parameters, average crystallite size, crystallinity percentage, lattice strain, stress, energy density and atomic packing factor) upon Sm doping is investigated together with Rietveld refinement and Le Bail analysis techniques. XRPD data confirmed that the synthesized nanostructures crystallize in a wurtzite hexagonal structure, the dopant Sm is incorporated into the Zn lattice and the annealing treatment plays a crucial role in determining the structural and optical properties of RE-metal-doped nanoparticles. Values of the optical band gap energy estimated from optical absorbance measurements reveal a widening of the band gap.
Keywords: X-ray powder diffraction; Rietveld analysis; Le Bail analysis; zinc oxide nanoparticles; doping effects